Rewinding and testing a 15 H.P. D.C. motor - Heim, Harry Russell; Wright, Earnest A. (My University, 1906)
Introduction: In treating this subject we shall not confine our discussions to the particular motor tested. We shall give a general discussion of the Direct Current motor under the heads of theory, and development. Under tests we shall discuss the particular motor under consideration. The greater part of our work does not appear in writing but in the motor which is operating successfully in the dynamo laboratory. Although the subject may appear as elementary, it is of the greatest importance. Notwithstanding the growing popularity of the induction motor the time is far distant when it will replace the direct current motor. In fact, the qualities of direct current make it possible to accomplish results with it that can never be hoped for in the A.C. motor. Yet in the present state of perfection of the D.C. motor, there are still desired improvements. Its efficiency at best is low and a simpler method of variation of speed would satisfy a long felt want. In the present method of power transmission the D.C. motor is half the problem, hence the man who is to solve it cannot understand its principle too well.
Citation: Heim, Harry Russell and Wright, Earnest A. Rewinding and testing a 15 H.P. D.C. motor. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Direct Current Motor; Induction Motor; Theses